Corporate governance - Hirschey, Mark; John, Kose; Makhija, Anil K. (Emerald, 2004)
This volume contains fourteen research papers with theoretical and empirical treatment of important financial aspects of corporate governance. The papers cover major corporate governance issues such as the role of the board of directors, ownership structure, ownership concentration, and the influence of outside blockholders. Another salient feature of this collection is that it offers substantial international evidence, including that from the United States of America, Australia, Germany, Saudi Arabia, China, India, and Malaysia.
Keywords: Corporate governance.; elektronické knihy; electronic books